PENGEMBANGAN TANAMAN HERBAL SEBAGAI DESTINASI WISATA DI DESA CATUR, KINTAMANI, BALI - Dermawan Waruwu; Ni Made Diana Erfiani; I Putu Darmawijaya; Natalia Sri Endah Kurniawati (LP2M Universitas Hasanuddin, 2020)
Development of Herbal Plants as a Tourist Destination in Catur Village, Kintamani, BaliAbstract. The people of Catur Village are classified as less prosperous economically but have the potential for natural products and cultural uniqueness. Quite a lot of natural products in this area in the form of coffee, oranges, lemongrass, sweet potatoes, ginger, turmeric, and so on. These natural products are classified as herbs that are beneficial to health. Natural products and cultural uniqueness have not been developed into tourist attractions because people lack knowledge and skills. The Partner Village Development Program (PPDM) is a solution to the problems faced by the community. The PPDM implementation team provides training and assistance to the Women Farmers Group (KWT) and Tourism Awareness Group (Pokdarwis). The purpose of implementing PPDM in Catur Village is that KWT and Pokdarwis have the knowledge and skills in developing their natural and cultural potential. This training and assistance resulted in three things: First, KWT and Pokdarwis members were able to cultivate herbal plants in their yard or garden; Second, KWT and Pokdarwis members are able to make coffee perfume and process coffee waste into cascara tea and coffee leaf tea; Third, KWT and Pokdarwis members are able to organize tourist attractions and make trekking paths in the tourist area. The development and promotion of this tourist village use technology and social media such as Facebook, Youtube, and other online media. Thus, the tourist area in Catur Village, Kintamani Bali becomes an educational and contemporary tourism destination based on herbs.Keywords: Herbal plants, herbal tourism, technology, Catur Village, Kintamani Bali.Abstrak: Masyarakat Desa Catur tergolong kurang sejahtera secara ekonomi, namun memiliki potensi hasil alam dan keunikan budaya. Hasil alam cukup banyak di daerah ini berupa kopi, jeruk, sereh, bunga gumitir, ubi, jahe, kunyit, dan sebagainya. Hasil alam ini tergolong sebagai tanaman herbal yang bermanfaat bagi kesehatan. Hasil alam maupun keunikan budaya belum dikembangkan menjadi objek wisata karena masyarakatnya kurang pengetahuan serta keterampilan. Program Pengembangan Desa Mitra (PPDM) menjadi solusi terhadap masalah yang dihadapi oleh masyarakat tersebut. Tim pelaksana PPDM memberikan pelatihan dan pendampingan kepada Kelompok Wanita Tani (KWT) dan Kelompok Sadar Wisata (Pokdarwis). Tujuan pelaksanaan PPDM di Desa Catur adalah agar KWT dan Pokdarwis memiliki pengetahuan serta keterampilan dalam mengembangkan potensi alam maupun budayanya.Pelatihan dan pendampingan ini menghasilkan tiga hal: Pertama, anggota KWT dan Pokdarwis mampu membudidayakan tanaman herbal di halaman rumah atau kebunnya; Kedua, anggota KWT dan Pokdarwis mampu membuat parfum kopi serta mengolah limbah kopi menjadi teh cerry kopi (cascara tea) dan teh daun kopi; Ketiga, anggota KWT dan Pokdarwis mampu menata objek wisata serta membuat jalur trekking di kawasan wisata tersebut. Pengembangan maupun promosi desa wisata ini menggunakan teknologi serta media sosial seperti facebook, youtube, dan media online lainnya. Dengan demikian, kawasan wisata di Desa Catur menjadi destinasi wisata edukasi dan kekinian yang berbasis pada herbal.Kata Kunci: Tanaman herbal, wisata herbal, teknologi, Desa Catur, Bali.